CN103909240B - A kind of compound copper sheathing and preparation method thereof - Google Patents
A kind of compound copper sheathing and preparation method thereof Download PDFInfo
- Publication number
- CN103909240B CN103909240B CN201410142619.6A CN201410142619A CN103909240B CN 103909240 B CN103909240 B CN 103909240B CN 201410142619 A CN201410142619 A CN 201410142619A CN 103909240 B CN103909240 B CN 103909240B
- Authority
- CN
- China
- Prior art keywords
- copper sheathing
- interior
- compound
- sheathing
- preparation
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Active
Links
- RYGMFSIKBFXOCR-UHFFFAOYSA-N Copper Chemical compound [Cu] RYGMFSIKBFXOCR-UHFFFAOYSA-N 0.000 title claims abstract description 246
- 229910052802 copper Inorganic materials 0.000 title claims abstract description 246
- 239000010949 copper Substances 0.000 title claims abstract description 246
- 150000001875 compounds Chemical class 0.000 title claims abstract description 54
- 238000002360 preparation method Methods 0.000 title claims abstract description 31
- 239000000463 material Substances 0.000 claims abstract description 37
- 238000001816 cooling Methods 0.000 claims abstract description 36
- QZLJNVMRJXHARQ-UHFFFAOYSA-N [Zr].[Cr].[Cu] Chemical compound [Zr].[Cr].[Cu] QZLJNVMRJXHARQ-UHFFFAOYSA-N 0.000 claims abstract description 14
- OKTJSMMVPCPJKN-UHFFFAOYSA-N Carbon Chemical group [C] OKTJSMMVPCPJKN-UHFFFAOYSA-N 0.000 claims description 12
- 239000007788 liquid Substances 0.000 claims description 12
- 239000000853 adhesive Substances 0.000 claims description 11
- 230000001070 adhesive effect Effects 0.000 claims description 11
- 238000010438 heat treatment Methods 0.000 claims description 8
- 229910021389 graphene Inorganic materials 0.000 claims description 6
- 229910002804 graphite Inorganic materials 0.000 claims description 6
- 239000010439 graphite Substances 0.000 claims description 6
- VYZAMTAEIAYCRO-UHFFFAOYSA-N Chromium Chemical compound [Cr] VYZAMTAEIAYCRO-UHFFFAOYSA-N 0.000 claims description 2
- VYPSYNLAJGMNEJ-UHFFFAOYSA-N Silicium dioxide Chemical compound O=[Si]=O VYPSYNLAJGMNEJ-UHFFFAOYSA-N 0.000 claims description 2
- QCWXUUIWCKQGHC-UHFFFAOYSA-N Zirconium Chemical compound [Zr] QCWXUUIWCKQGHC-UHFFFAOYSA-N 0.000 claims description 2
- 229910052804 chromium Inorganic materials 0.000 claims description 2
- 239000011651 chromium Substances 0.000 claims description 2
- 239000000741 silica gel Substances 0.000 claims description 2
- 229910002027 silica gel Inorganic materials 0.000 claims description 2
- 229910052726 zirconium Inorganic materials 0.000 claims description 2
- 239000000498 cooling water Substances 0.000 description 12
- 238000000034 method Methods 0.000 description 7
- 238000012546 transfer Methods 0.000 description 6
- 229910000831 Steel Inorganic materials 0.000 description 4
- 239000013078 crystal Substances 0.000 description 4
- 230000000694 effects Effects 0.000 description 4
- 239000010959 steel Substances 0.000 description 4
- 238000005266 casting Methods 0.000 description 3
- 238000010586 diagram Methods 0.000 description 3
- 230000003628 erosive effect Effects 0.000 description 3
- 238000005242 forging Methods 0.000 description 3
- 238000003754 machining Methods 0.000 description 3
- 238000002844 melting Methods 0.000 description 3
- 230000008018 melting Effects 0.000 description 3
- 230000015572 biosynthetic process Effects 0.000 description 2
- 229910000881 Cu alloy Inorganic materials 0.000 description 1
- 239000012141 concentrate Substances 0.000 description 1
- 230000007812 deficiency Effects 0.000 description 1
- 238000005474 detonation Methods 0.000 description 1
- 238000005516 engineering process Methods 0.000 description 1
- 238000002474 experimental method Methods 0.000 description 1
- 238000002309 gasification Methods 0.000 description 1
- 238000004519 manufacturing process Methods 0.000 description 1
- 238000000465 moulding Methods 0.000 description 1
- 238000012827 research and development Methods 0.000 description 1
- XLYOFNOQVPJJNP-UHFFFAOYSA-N water Substances O XLYOFNOQVPJJNP-UHFFFAOYSA-N 0.000 description 1
Landscapes
- Other Surface Treatments For Metallic Materials (AREA)
Abstract
Compound copper sheathing is used in the open a kind of cooling of the present invention, described compound copper sheathing comprises the outer copper sheathing fitted tightly together, horizontal high thermal conductivity material layer and interior copper sheathing from outside to inside successively, described outer copper sheathing adopts chromium zirconium copper to be prepared from, and described outer copper sheathing adopts oxygen-free copper to be prepared from.Complex copper cover of the present invention has higher cooling effectiveness, can promote the performance of amorphous, nanocrystalline product, improves the product percent of pass of amorphous, nanocrystalline carrying device processed simultaneously.Meanwhile, the invention also discloses the preparation method of described compound copper sheathing.
Description
Technical field
The present invention relates to a kind of for copper cooling copper sheathing and preparation method thereof, especially a kind of for cooling copper sheathing and preparation method thereof in the preparation such as amorphous, nanocrystalline strip.
Background technology
Existing copper cooling copper sheathing cooling velocity is limited to the thermal conductivity of copper alloy, and in common amorphous, nanocrystalline strip production process, its cooling effect still can meet the demands.But the amorphous nano-crystalline product higher for ask for something, the cooling effect of existing copper cooling copper sheathing cannot satisfy the demands.Mainly because:
One, the thickness of existing copper sheathing is 30mm to 50mm, as shown in figure 1 and 2, when molten steel 2 contacts with cooling copper sheathing 1, the heat of molten steel 2 will concentrate the cooling water 3 of vertically Directed cooling copper sheathing 1 inside, very high owing to cooling copper sheathing 1 temperature herein, less with cooling water 3 contact area, cooling water 3 is easily made to produce gasification, the thermal conductivity of air is equivalent to about 1/25th of water, cause the actual heat transfer efficiency between cooling copper sheathing 1 and cooling water 3 significantly to reduce, affect the stability of amorphous moulding process.
Two, existing copper sheathing thermal conductivity factor made of copper is 330W/m.k, lower than the 400-410W/m.k of oxygen-free copper, more lower than the 1200-1500W/m.k of graphite heat-conducting fin and the 5000W/m.k of Graphene.
Therefore, need a kind of new-type cooling copper sheathing of research and development badly, so that effectively cooling effectiveness can be promoted, thus promote amorphous, the performance of nanocrystalline product and the product percent of pass of amorphous nano-crystalline carrying device.
Summary of the invention
The object of the invention is to overcome the deficiencies in the prior art part and the compound copper sheathing that a kind of heat transfer efficiency is higher, have uniform cooling, can improve the product percent of pass of amorphous nano-crystalline carrying device is provided; Meanwhile, present invention also offers the preparation method of described compound copper sheathing.
For achieving the above object, the technical scheme that the present invention takes is: a kind of compound copper sheathing, described compound copper sheathing comprises the outer copper sheathing fitted tightly together, horizontal high thermal conductivity material layer and interior copper sheathing from outside to inside successively, described outer copper sheathing adopts chromium zirconium copper to be prepared from, and described outer copper sheathing adopts oxygen-free copper to be prepared from.
In horizontal high thermal conductivity material layer of the present invention, horizontal high thermal conductivity material refers to the material of transverse thermal conductivity higher than the 400-410W/m.k of oxygen-free copper.
Compound copper sheathing of the present invention, be followed successively by the outer copper sheathing fitted tightly together, horizontal high thermal conductivity material layer and interior copper sheathing from outside to inside, described outer copper sheathing adopts chromium zirconium copper to be prepared from, chromium zirconium copper has the characteristic of wear-resisting, high temperature resistant erosion, be placed on the outside of compound copper sheathing, be conducive to the service life extending compound copper sheathing of the present invention.Horizontal high thermal conductivity material layer is provided with between described outer copper sheathing and interior copper sheathing, described horizontal high thermal conductivity material layer is for having the material of horizontal high thermal conductivity, the heat that outer copper sheathing can be made to receive conducts to surrounding, add efficiently radiates heat area, strengthen the cooling effectiveness of outer copper sheathing, prevent hot-spot and internal cooling water.Described interior copper sheathing adopts oxygen-free copper to be prepared from, and the interior copper sheathing utilizing oxygen-free copper to prepare and the higher feature of the heat-exchange capacity of cooling water, effectively improve the cooling uniformity of compound copper sheathing of the present invention, make strip quality more stable.
As the preferred embodiment of compound copper sheathing of the present invention, the thickness of described outer copper sheathing is 5 ~ 30mm, and the thickness of described horizontal high thermal conductivity material layer is 0.1 ~ 1.5mm, and the thickness of described outer copper sheathing is 5 ~ 15mm.The thickness of outer copper sheathing should not be greater than 30mm, otherwise heat transfer can be made apart from long, and then is that surface temperature is too high, is unfavorable for amorphous formation, and certainly, the thickness of described outer copper sheathing also should not be less than 5mm, and not so insufficient strength, the life-span is short.The thickness of described horizontal high thermal conductivity material layer is not more than 1.5mm, if the too thick high cost of thickness, and affects the structural stability of copper sheathing entirety.The thickness of described interior copper sheathing should not be greater than 15mm, blocked uply will affect heat transfer distance, and affect radiating efficiency, promote outer copper sheathing surface temperature, affect amorphous formation, the thickness of described interior copper sheathing should not be less than 5mm, otherwise insufficient strength.
As the preferred embodiment of compound copper sheathing of the present invention, described horizontal high thermal conductivity material layer is Graphene or graphite heat-conducting fin.Described horizontal high thermal conductivity material layer selects Graphene or graphite heat-conducting fin, the thermal conductivity factor of Graphene or graphite heat-conducting fin is respectively Graphene 5000W/m.k, graphite heat-conducting fin 1200-1500W/m.k, there is the thermal conductivity factor far above existing copper sheathing, the heat that outer copper sheathing receives can be conducted to surrounding, increase efficiently radiates heat area, strengthen the cooling effectiveness of outer copper sheathing, prevent hot-spot and internal cooling water.
As the preferred embodiment of compound copper sheathing of the present invention, in the chromium zirconium copper that described outer copper sheathing adopts, the mass percentage of chromium is 0.5 ~ 1.5%, and the mass percentage of zirconium is 0.08 ~ 0.3%, and surplus is copper.
In addition, present invention also offers the preparation method of described compound copper sheathing, said method comprising the steps of:
(1) preparation of outer copper sheathing: adopt chromium zirconium copper for outer copper sheathing;
(2) preparation of interior copper sheathing: adopt copper sheathing in oxygen-free copper preparation;
(3) the interior copper sheathing outer surface prepared in step (2) evenly pastes horizontal high thermal conductivity material layer;
(4) by outer copper sheathing expanded by heating or the cooling of interior copper sheathing reduced or interior copper sheathing cooling reduced while outer copper sheathing expanded by heating, the internal diameter to described outer copper sheathing is greater than the external diameter of described interior copper sheathing;
(5) outer surface is pasted with copper sheathing in horizontal high thermal conductivity material layer and is placed in internal diameter becomes large outer copper sheathing because of expanded by heating, naturally cool, obtain compound copper sheathing.
In described step (1) and step (2), inside and outside smooth outer copper sheathing and interior copper sheathing can be made by techniques such as melting, casting, forging, machining, rubbing downs.
As the preferred embodiment of the preparation method of compound copper sheathing of the present invention, the external diameter of the interior copper sheathing prepared in described step (2) is more than or equal to the internal diameter of the outer copper sheathing that step (1) prepares.As the more preferably embodiment of the preparation method of compound copper sheathing of the present invention, the difference in internal diameters of the outer copper sheathing that the external diameter of the interior copper sheathing that described step (2) prepares and step (1) prepare is not more than 5mm, if the external diameter of interior copper sheathing is more too many greatly than the internal diameter of outer copper sheathing, interior copper sheathing can be there is and be not easily placed in problem in outer copper sheathing, therefore preferably in the external diameter of copper sheathing than within the large 5mm of the internal diameter of outer copper sheathing.
As the preferred embodiment of the preparation method of compound copper sheathing of the present invention, adopt adhesive to be pasted onto on the outer surface of interior copper sheathing by horizontal high thermal conductivity material layer in described step (3), described adhesive can bear the variations in temperature of-30 ~ 300 DEG C.Described horizontal high thermal conductivity material layer pastes the outer surface at interior copper sheathing by adhesive, and described adhesive needs the variations in temperature can bearing-30 ~ 300 DEG C, to prevent from preparing gained complex copper cover in use, adhesive failure.The outer surface of described interior copper sheathing evenly can paste the horizontal high thermal conductivity material layer of one deck or more.Described adhesive preferably but be not limited to HBC1099 heat conductive silica gel, thermal conductivity coefficient 0.86W/(mK), serviceability temperature-60 ~ 300 DEG C.
As the preferred embodiment of the preparation method of compound copper sheathing of the present invention, in described step (4), outer copper sheathing is soaked in high-temp liquid and make the internal diameter of outer copper sheathing be expanded to the external diameter being greater than described interior copper sheathing; Or being soaked in cryogenic liquid by described interior copper sheathing makes the external diameter of interior copper sheathing be contracted to the internal diameter being less than described outer copper sheathing; Or soaked in high-temp liquid by outer copper sheathing while making the internal diameter of outer copper sheathing expand, soaked in cryogenic liquid by interior copper sheathing and make the external diameter of interior copper sheathing shrink, the internal diameter to described outer copper sheathing is greater than the external diameter of described interior copper sheathing.Described high-temp liquid preferably but be not limited to high-temperature hot oil.
Compound copper sheathing of the present invention, comprise the outer copper sheathing, the horizontal high thermal conductivity material layer that are prepared from by chromium zirconium copper successively and copper sheathing three kinds of different materials are formed in being prepared from by oxygen-free copper, chromium zirconium copper has the characteristic of wear-resisting, high temperature resistant erosion, be placed on the outside of compound copper sheathing, be conducive to the service life extending described compound copper sheathing; Described horizontal high thermal conductivity material layer is for having the material of horizontal high thermal conductivity, and the heat that outer copper sheathing can be made to receive conducts to surrounding, adds efficiently radiates heat area, strengthens the cooling effectiveness of outer copper sheathing, prevent hot-spot and internal cooling water; Described interior copper sheathing adopts oxygen-free copper to be prepared from, and the interior copper sheathing utilizing oxygen-free copper to prepare and the higher feature of the heat-exchange capacity of cooling water, effectively improve the cooling uniformity of compound copper sheathing of the present invention, make strip quality more stable.The preparation method of compound copper sheathing of the present invention, simple to operate, facilitate industrialization promotion to use.
Accompanying drawing explanation
Fig. 1 is the structural representation adopting existing cooling copper sheathing non-crystal belt making.
Fig. 2 is heat transfer schematic diagram when adopting existing cooling copper sheathing non-crystal belt making.
Fig. 3 is the structural representation of a kind of embodiment of compound copper sheathing of the present invention.
Fig. 4 is the detonation configuration schematic diagram of the copper sheathing of compound shown in Fig. 3.
Fig. 5 is heat transfer schematic diagram when adopting Compound cooling copper sheathing non-crystal belt making of the present invention.
In figure, 1 for cooling copper sheathing, 2 be copper liquid, 3 for cooling water, 4 for amorphous steel band, 5 for heat conduction direction, 10 for outer copper sheathing, 20 for horizontal high thermal conductivity material layer, 30 be interior copper sheathing.
Detailed description of the invention
For better the object, technical solutions and advantages of the present invention being described, below in conjunction with the drawings and specific embodiments, the invention will be further described.
Embodiment 1
A kind of embodiment of compound copper sheathing of the present invention, as shown in Figure 3, compound copper sheathing described in the present embodiment comprises the outer copper sheathing 10 fitted tightly together, horizontal high thermal conductivity material layer 20 and interior copper sheathing 30 from outside to inside successively, the thickness of described outer copper sheathing 10 is 5 ~ 30mm, the thickness of described horizontal high thermal conductivity material layer 20 is 0.1 ~ 1.5mm, the thickness of described interior copper sheathing 30 is 5 ~ 15mm, and those skilled in the art can select the outer copper sheathing of suitable thickness, horizontal high thermal conductivity material layer and interior copper sheathing according to actual needs.
As shown in Figure 4, compound copper sheathing described in the present embodiment adopts following methods to be prepared from:
(1) preparation of outer copper sheathing: adopt chromium zirconium copper by inside and outside smooth outer copper sheathings 10 of technique preparation such as melting, casting, forging, machining, rubbing downs;
(2) preparation of interior copper sheathing: adopt oxygen-free copper by copper sheathing 30 in the inside and outside smooth preparations of technique preparation such as melting, casting, forging, machining, rubbing down, the external diameter of described interior copper sheathing is more than or equal to the internal diameter of the outer copper sheathing that step (1) prepares, and the difference in internal diameters of outer copper sheathing that the external diameter of described interior copper sheathing and step (1) prepare is not more than 5mm;
(3) interior copper sheathing 30 outer surface prepared in step (2) adopts adhesive evenly to paste the horizontal high thermal conductivity material layer 20 of one deck or more, and described adhesive can bear the variations in temperature of-30 ~ 300 DEG C;
(4) outer copper sheathing 10 is soaked in high-temperature hot oil, make outer copper sheathing 10 internal diameter become the external diameter that the large internal diameter to described outer copper sheathing 10 is greater than described interior copper sheathing 30 because of expanded by heating;
(5) outer surface is pasted with copper sheathing 30 in horizontal high thermal conductivity material layer 20 and is placed in internal diameter becomes large outer copper sheathing 10 because of expanded by heating, naturally cool, obtain compound copper sheathing.
In the preparation method of the present embodiment compound copper sheathing described above, in described step (4), described interior copper sheathing 30 can also be soaked in cryogenic liquid and make the external diameter of interior copper sheathing 30 be contracted to the internal diameter being less than described outer copper sheathing 10; Or soaked in high-temperature hot oil by outer copper sheathing 10 while making the internal diameter of outer copper sheathing 10 expand, soaked in cryogenic liquid by interior copper sheathing 30 and make the external diameter of interior copper sheathing 30 shrink, the internal diameter to described outer copper sheathing 10 is greater than the external diameter of described interior copper sheathing 30.
Compound copper sheathing described in the present embodiment, outer copper sheathing 10 adopts chromium zirconium copper to be prepared from, and chromium zirconium copper has the characteristic of wear-resisting, high temperature resistant erosion, is placed on the outside of compound copper sheathing, is conducive to the service life extending compound copper sheathing.When adopting compound copper sheathing non-crystal belt making described in the present embodiment, as shown in Figure 5, owing to being provided with horizontal high thermal conductivity material layer 20 between outer copper sheathing 10 and interior copper sheathing 30, described horizontal high thermal conductivity material layer 20 is for having the material of horizontal high thermal conductivity, the heat that outer copper sheathing 10 can be made to receive conducts to surrounding, add efficiently radiates heat area, strengthen the cooling effectiveness of outer copper sheathing 10, prevent hot-spot and internal cooling water.And because interior copper sheathing 30 adopts oxygen-free copper to be prepared from, the feature that the interior copper sheathing 30 utilizing oxygen-free copper to prepare is higher with the heat-exchange capacity of cooling water 3, effectively improves the cooling uniformity of compound copper sheathing of the present invention, makes strip quality more stable.
Embodiment 2
The cooling effect experiment of compound copper sheathing of the present invention
Use 100kg level amorphous strip maker to carry out system band, one-tenth brand is 1k101, and molten steel temperature controls at 1000 ~ 1450 DEG C, and adopt existing cooling copper sheathing and complex copper cover of the present invention to cool respectively, experimental result is as shown in table 1:
Table 1 cooling effect contrasts
| Project | Compound copper sheathing of the present invention | Existing cooling copper sheathing promotes |
| Band process chill roll surface temperature processed | 97.5℃ | 112.7℃15.2℃ |
| Ten thousand metres amorphous ribbon on average breaks end quantity | 5.5 | 7.223.6% |
| On average break end after ten thousand metres heat treatment quantity | 9.4 | 12.826.5% |
| Comprehensive yields | 78.4% | 74.2%5.7% |
As seen from Table 1, compound copper sheathing of the present invention effectively can improve cooling effectiveness, improves the performance of amorphous, nanocrystalline product, and the product percent of pass of amorphous nano-crystalline carrying device.
Finally to should be noted that; above embodiment is only in order to illustrate technical scheme of the present invention but not limiting the scope of the invention; although be explained in detail the present invention with reference to preferred embodiment; those of ordinary skill in the art is to be understood that; can modify to technical scheme of the present invention or equivalent replacement, and not depart from essence and the scope of technical solution of the present invention.
Claims (9)
1. a compound copper sheathing, it is characterized in that, described compound copper sheathing comprises the outer copper sheathing fitted tightly together, horizontal high thermal conductivity material layer and interior copper sheathing from outside to inside successively, and described outer copper sheathing adopts chromium zirconium copper to be prepared from, and described interior copper sheathing adopts oxygen-free copper to be prepared from;
Described horizontal high thermal conductivity material layer is Graphene or graphite heat-conducting fin.
2. compound copper sheathing as claimed in claim 1, it is characterized in that, the thickness of described outer copper sheathing is 5 ~ 30mm, and the thickness of described horizontal high thermal conductivity material layer is 0.1 ~ 1.5mm, and the thickness of described interior copper sheathing is 5 ~ 15mm.
3. compound copper sheathing as claimed in claim 1, is characterized in that, in the chromium zirconium copper that described outer copper sheathing adopts, the mass percentage of chromium is 0.5 ~ 1.5%, and the mass percentage of zirconium is 0.08 ~ 0.3%, and surplus is copper.
4. a preparation method for compound copper sheathing as described in as arbitrary in claims 1 to 3, is characterized in that, comprise the following steps:
(1) preparation of outer copper sheathing: adopt chromium zirconium copper for outer copper sheathing;
(2) preparation of interior copper sheathing: adopt copper sheathing in oxygen-free copper preparation;
(3) the interior copper sheathing outer surface prepared in step (2) evenly pastes horizontal high thermal conductivity material layer;
(4) by outer copper sheathing expanded by heating or the cooling of interior copper sheathing reduced or interior copper sheathing cooling reduced while outer copper sheathing expanded by heating, the internal diameter to described outer copper sheathing is greater than the external diameter of described interior copper sheathing;
(5) outer surface is pasted with copper sheathing in horizontal high thermal conductivity material layer and is placed in outer copper sheathing, naturally cool, obtain compound copper sheathing.
5. the preparation method of compound copper sheathing as claimed in claim 4, it is characterized in that, the external diameter of the interior copper sheathing prepared in described step (2) is more than or equal to the internal diameter of the outer copper sheathing that step (1) prepares.
6. the preparation method of compound copper sheathing as claimed in claim 5, it is characterized in that, the difference in internal diameters of the outer copper sheathing that the external diameter of the interior copper sheathing that described step (2) prepares and step (1) prepare is not more than 5mm.
7. the preparation method of compound copper sheathing as claimed in claim 4, it is characterized in that, adopt adhesive to be pasted onto on the outer surface of interior copper sheathing by horizontal high thermal conductivity material layer in described step (3), described adhesive can bear the variations in temperature of-30 ~ 300 DEG C.
8. the preparation method of compound copper sheathing as claimed in claim 7, it is characterized in that, described adhesive is heat conductive silica gel.
9. the preparation method of compound copper sheathing as claimed in claim 4, is characterized in that, soaked by outer copper sheathing and make the internal diameter of outer copper sheathing be expanded to the external diameter being greater than described interior copper sheathing in described step (4) in high-temp liquid; Or being soaked in cryogenic liquid by described interior copper sheathing makes the external diameter of interior copper sheathing be contracted to the internal diameter being less than described outer copper sheathing; Or soaked in high-temp liquid by outer copper sheathing while making the internal diameter of outer copper sheathing expand, soaked in cryogenic liquid by interior copper sheathing and make the external diameter of interior copper sheathing shrink, the internal diameter to described outer copper sheathing is greater than the external diameter of described interior copper sheathing.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201410142619.6A CN103909240B (en) | 2014-04-10 | 2014-04-10 | A kind of compound copper sheathing and preparation method thereof |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201410142619.6A CN103909240B (en) | 2014-04-10 | 2014-04-10 | A kind of compound copper sheathing and preparation method thereof |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN103909240A CN103909240A (en) | 2014-07-09 |
| CN103909240B true CN103909240B (en) | 2016-01-27 |
Family
ID=51035415
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201410142619.6A Active CN103909240B (en) | 2014-04-10 | 2014-04-10 | A kind of compound copper sheathing and preparation method thereof |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN103909240B (en) |
Families Citing this family (3)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104694780B (en) * | 2015-02-06 | 2017-04-26 | 北京电力自动化设备有限公司 | Cu-Ni-Si alloy material and cooling roller sleeve containing alloy |
| CN110517837A (en) * | 2018-05-21 | 2019-11-29 | 灯达(深圳)电器有限公司 | A kind of highly sensitive self- recoverage insurance using self breakaway-element of graphene energy |
| CN108555259A (en) * | 2018-06-29 | 2018-09-21 | 王春龙 | A kind of chill roll and equipment producing amorphous band |
Citations (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US3715265A (en) * | 1969-09-03 | 1973-02-06 | Mc Donnell Douglas Corp | Composite thermal insulation |
| CN2213035Y (en) * | 1994-08-16 | 1995-11-22 | 吕爱菊 | Thermometal compounded horizontal continuous casting crystallizer internal member |
| CN1260403A (en) * | 1999-01-13 | 2000-07-19 | 陈丕文 | Copper alloy for copper jacket of horizontal continuous casting crystallizer and its technology |
| CN2538452Y (en) * | 2002-05-15 | 2003-03-05 | 黄光雷 | Composite copper cover for prestress mould |
| CN103056319A (en) * | 2013-01-28 | 2013-04-24 | 青岛云路新能源科技有限公司 | Structure of copper bush of amorphous crystallizer |
| CN103567402A (en) * | 2012-07-19 | 2014-02-12 | 常州市武进长虹结晶器有限公司 | Production process for chromium-zirconium-copper copper pipes |
-
2014
- 2014-04-10 CN CN201410142619.6A patent/CN103909240B/en active Active
Patent Citations (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US3715265A (en) * | 1969-09-03 | 1973-02-06 | Mc Donnell Douglas Corp | Composite thermal insulation |
| CN2213035Y (en) * | 1994-08-16 | 1995-11-22 | 吕爱菊 | Thermometal compounded horizontal continuous casting crystallizer internal member |
| CN1260403A (en) * | 1999-01-13 | 2000-07-19 | 陈丕文 | Copper alloy for copper jacket of horizontal continuous casting crystallizer and its technology |
| CN2538452Y (en) * | 2002-05-15 | 2003-03-05 | 黄光雷 | Composite copper cover for prestress mould |
| CN103567402A (en) * | 2012-07-19 | 2014-02-12 | 常州市武进长虹结晶器有限公司 | Production process for chromium-zirconium-copper copper pipes |
| CN103056319A (en) * | 2013-01-28 | 2013-04-24 | 青岛云路新能源科技有限公司 | Structure of copper bush of amorphous crystallizer |
Also Published As
| Publication number | Publication date |
|---|---|
| CN103909240A (en) | 2014-07-09 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN102103906B (en) | Method for preparing copper-coated aluminium composite material | |
| CN102133582B (en) | Mold/non-mode combined pulling process and device | |
| CN101249512A (en) | Magnesium alloy plate rolling roll heating system | |
| CN204757778U (en) | Foamed metal heat transfer structure | |
| CN103909240A (en) | Composite copper bush and preparation method thereof | |
| CN204262069U (en) | Roll rear cold bed attemperator | |
| CN103272844A (en) | Device and method for rolling magnesium alloy at different temperatures | |
| CN208501086U (en) | A kind of rotary target material bonded | |
| CN103193032A (en) | Cold storage box after double-layer sheathing and rear vacuumizing layer | |
| CN108555427B (en) | High-frequency welding device for small-diameter thick-wall pipe | |
| CN202713647U (en) | Nano electric heating coil of injection molding machine | |
| CN103706777A (en) | Ferrous metal liquid die forging mould and manufacturing method thereof | |
| CN204093364U (en) | A kind of glue electrical heating stirring tank | |
| CN202111879U (en) | Integral formed type heating disc used for electric kettle | |
| CN207537550U (en) | A kind of anode claw for electrolytic aluminium | |
| CN202534545U (en) | Conductive roller used in capacitor aluminum foil production | |
| CN209787499U (en) | Electromagnetic heating induction coil made of high-temperature-resistant alloy steel material | |
| CN207678027U (en) | Peak-Valley Phase Change Heating Device Based on Electromagnetic Induction Heating | |
| CN105728655A (en) | Reusable graphite gating and feeding hole | |
| CN202984329U (en) | Nitrogen-cooled die core for thick-wall large-diameter aluminum alloy round pipe extrusion die | |
| CN211994362U (en) | Carbon element compression molding mould external mold heating structure | |
| CN203923305U (en) | A kind of copper-clad aluminum conductor annealing device | |
| CN204724614U (en) | Hollow copper ingot continuous heating | |
| CN221848235U (en) | Heatable die sleeve for extruding magnesium alloy and hard aluminum alloy section bar | |
| CN203586916U (en) | Anti-corrosive pipe plate for shell-and-tube type heat exchanger |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| C06 | Publication | ||
| PB01 | Publication | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| C14 | Grant of patent or utility model | ||
| GR01 | Patent grant |